The practise of strategic compensation in Malaysian five-star beach resort hotels - Ahmad, Rozila; Scott, Noel; Solnet, David (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
The development of a sound management and staff compensation plan is crucial for business success. This study assesses the relevance of strategic compensation in developing countries by investigating the strategic compensation practise in Malaysian five-star hotels. Focusing on managerial and non-managerial employees, it finds that there is considerable variation in the extent of strategic compensation adoption in these hotels despite the similarities of their target market, star rating and external environment. The adoption of strategic compensation also varies within the hotels to match the system with employees' perceived strategic value. While some hotels adopt compensation based on seniority, others compensate managerial employees based on performance with some preference for the later. Although the findings raises some issues which requires future quantitative research, the present findings provide some suggestions on how to improve the compensation systems for five-star beach resort hotels in Malaysia and potentially in other countries with similar environment such as Thailand and Indonesia.